ICU-Mortality in Old and Very Old Patients Suffering From Sepsis and Septic Shock - Bruno, Raphael Romano; Wernly, Bernhard; Mamandipoor, Behrooz; Rezar, Richard; Binnebössel, Stephan; Baldia, Philipp Heinrich; Wolff, Georg; Kelm, Malte; Guidet, Bertrand; De Lange, Dylan W.; Dankl, Daniel; Koköfer, Andreas; et al. (Frontiers in Medicine, 2021)
Purpose Old (>64 years) and very old (>79 years) intensive care patients with sepsis suffer from high mortality. In the very old, the value of critical care has been questioned. We aimed to compare the mortality, rates of organ support and the length of stay in old vs. very old patients with sepsis and septic shock in intensive care. Methods This analysis included 9385 patients with sepsis; 6184 were old (aged 65 to 79 years), and 3201 were very old patients (aged 80 years and older) from the multi-center eICU Collaborative Research Database. A multilevel logistic regression analysis was used to fit three sequential regression models for the binary primary outcome of ICU mortality. Further, a sensitivity analysis in septic shock patients (n=1054) was conducted. Results The median length of stay was shorter (50±67 vs. 56±72 hours;p <0.001) in the very old. Accordingly, the rates of prolonged stays were lower in the very old (>168 hours; 9% vs 12%; p<0.001). The mortality from sepsis was higher in very old patients (13% vs 11%; p=0.005), and after multivariable adjustment being very old was associated with higher odds for ICU mortality (aOR 1.32 95%CI 1.09-1.59; p=0.004). In patients with septic shock, mortality was also higher in the very old patients (38% vs 36%; aOR 1.50 95%CI 1.10-2.06; p=0.01). Conclusion Very old ICU-patients suffer from a slightly higher ICU mortality compared to old ICU-patients. However, despite the statistically significant differences in mortality, the clinical relevance of such minor differences is probably negligible.